Patient dose monitoring software in radiology - Maria P. Shatenok; Sergey A. Ryzhov; Zoya A. Lantukh; Yuliya V. Druzhinina; Kirill V. Tolkachev (Digital Diagnostics, 2022)
An increase in the number of diagnostic procedures using ionizing radiation (computed tomography, interventional procedures, and the use of nuclear medicine) results in an increase in radiation exposure and, consequently, an increase in collective and individual doses of radiation to patients.